Just and unjust wars a moral argument with historical illustrations - Walzer, Michael (Basic Books, a member of the Perseus Books Group, 2015)
"First published in 1977 and now brought up to the present with a new preface and postscript, this classic work by political philosopher Michael Walzer examines the moral issues that arise before, during, and after the wars we fight. Reaching from the Athenian attack on Melos, to the Mai Lai massacre, to Afghanistan and beyond, Walzer mines historical accounts and the testimony of participants, decision makers, and victims to explain when war is justified and what ethical limitations apply to those who wage it." -- back cover.